1975
DOI: 10.1080/17450397509423183
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Umsatz von14C-15N-Azetamid bei Schafen

Abstract: 4 male sheep (average weight: 53.5 kgs) were fed a semisynthetic diet containing acetamide as sole source of nitrogen. At the beginning of the trial twin-labelled 15N-14C-acetamide was administered by way of a ruminal fistula. The curve pattern of 14C activity in the TCE-soluble fraction of the ruminal fluid showed a synchronous behaviour in all animals beginning at 3 hours after the beginning of the trial. A half-life of 2 1/2 hours for the rate of absorption of 14C acetamide and deaminated 14C acetate was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Adam et al also dosed sheep with labeled acetamide directly in the rumen and noted that peak urine accumulation of 15N occurred after only 8 h. 30 Furthermore, the acetamide appeared to be virtually eliminated from the rumen within 15 h in that study, which is also consistent with our findings of rapid reduction of acetamide from milk following removal from the diet. Likewise, labeled carbon from acetamide fed to sheep declined in the rumen with a half-life of 2.5 h. 14 Additional studies will be necessary to further delineate the metabolism and excretion of acetamide in large ruminant animals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adam et al also dosed sheep with labeled acetamide directly in the rumen and noted that peak urine accumulation of 15N occurred after only 8 h. 30 Furthermore, the acetamide appeared to be virtually eliminated from the rumen within 15 h in that study, which is also consistent with our findings of rapid reduction of acetamide from milk following removal from the diet. Likewise, labeled carbon from acetamide fed to sheep declined in the rumen with a half-life of 2.5 h. 14 Additional studies will be necessary to further delineate the metabolism and excretion of acetamide in large ruminant animals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While acetamide can be metabolized in the rumen by amidase enzymes into acetate and ammonium, any acetamide that is not metabolized in the rumen could enter the milk or meat, in which case the feed contaminant would also become a food contaminant. Previous research suggests that acetamide can pass through the rumen wall and thus may enter the bloodstream. Recently, it has been shown that acetamide is already present as a food contaminant in many foods, including milk, beef, roasted coffee, and chicory root …”
Section: Introductionmentioning
confidence: 99%